Fenomena Pencarian Validasi pada Mahasiswa Generasi Z di Universitas Islam Ahmad Dahlan Sinjai - Suriyati, Suriyati; Mustamir, Mustamir; Syargawir, Syargawir; Ananda, Aulia; Aroepala, Syahrina Iman (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
The tendency to seek validation has increasingly emerged among Generation Z university students who grow up within digital as well as social media –driven environments. This study aims to analyze the manifestations of validation-seeking behavior, the underlying contributing factors, and its psychological and social implications for Gen-Z students. This study employs a qualitative approach research with a descriptive approach. Data collection techniques include in-depth interviews and observations of students in the Islamic Religious Education study program, with data analysis using thematic thecniques. The results indicate that validation seeking appears in several forms, including the desire for recognition on social media, the need for peer approval, and efforts to comply with perceived social expectations. Contributing factors consist of social pressure, digital identity construction, fear of missing out (FOMO), and emotional acceptance needs.The impacts are ambivalent: while validation can enhance motivation and confidence, it may also generate anxiety, dependence on external evaluations, and reduced psychological well-being.This study offers a deeper understanding of Gen-Z